Measurements and Analysis of Electromagnetic Compatibility of Railway Rolling Stock with Train Detection Systems Using Track Circuits - Adam Garczarek; Dorota Stachowiak (Energies)
One of the main challenges in the operation of electric traction vehicles is ensuring safety and operational reliability. To ensure the safety of railway traffic, vehicles must undergo a series of tests related to the investigation of disturbances generated, among others, in the return current to the mains. This problem is further complicated by the inability to perform such measurements under laboratory conditions. The implementation of tests under real conditions determines the appearance of additional potential interference sources, from power sources to improper interactions between current collectors and the overhead contact system, and it requires strict compliance with regulatory standards and the implementation of standardized testing procedures. This article presents issues related to the investigation and analysis of the electromagnetic compatibility of rolling stock with train detection systems using track circuits. The aim of these tests is to determine the harmonic components in the traction current in relation to the permissible levels specified in the latest editions of the European Railway Agency—ERA/ERTMS/033281 version 5.0 documents and Annex S-02 to the List of the President of the Office of Rail Transport. The measurement methodology and test procedures are presented in detail with respect to current legal requirements.